Groot Kunstconcert : maandag 26 januari 1948 - Schellens, A.; Verheyen, E.; De Mulder, J.; Gorlé, J.; Ardenois, August (Antwerpen: Concerten De Werker, 1948)
"met medewerking van : A. Schellens, E. Verheyen, J. De Mulder, J. Gorlé , Harmonie De Werker, A. Ardenois"